2023
DOI: 10.1111/jdi.14091
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic skin response for early detection of type 2 diabetic peripheral neuropathy and nephropathy

Hongying Liu,
Sheng Tan,
Zhenyu Ma
et al.

Abstract: BackgroundDiabetic peripheral neuropathy (DPN) and diabetic nephropathy (DN) are common complications of type 2 diabetes mellitus (T2DM). Although nerve conduction studies (NCS) and sympathetic skin response (SSR) can detect DPN, the more sensitive method for early diagnosis remains unclear. Furthermore, whether DPN can be used as a predictor for diabetic nephropathy needs clarification.MethodsWe evaluated nerve conduction studies, sympathetic skin response, and the diabetic nephropathy indicator microalbuminu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The ability of the area under the curve to diagnose DPN was 0.663, and the apical cut‐off value was 56 ms. Sudomotor function was also useful for the early diagnosis of peripheral artery disease when combined with the ankle‐brachial index in patients with type 2 diabetes 13 . The sympathetic skin response identified using Synergy Mobile (Oxford, UK) showed that the latency of the sympathetic skin response was significantly higher in patients with type 2 diabetes than in healthy controls 14 . The sensitivity of the sympathetic skin response for detecting DPN was 83.3%.…”
Section: Autonomic Neuropathymentioning
confidence: 99%
“…The ability of the area under the curve to diagnose DPN was 0.663, and the apical cut‐off value was 56 ms. Sudomotor function was also useful for the early diagnosis of peripheral artery disease when combined with the ankle‐brachial index in patients with type 2 diabetes 13 . The sympathetic skin response identified using Synergy Mobile (Oxford, UK) showed that the latency of the sympathetic skin response was significantly higher in patients with type 2 diabetes than in healthy controls 14 . The sensitivity of the sympathetic skin response for detecting DPN was 83.3%.…”
Section: Autonomic Neuropathymentioning
confidence: 99%